In vitro release and In vivo biocompatibility studies of biomimetic multilayered alginate-chitosan/β-TCP scaffold for osteochondral tissue. Issue 5 (23rd March 2016) - Algul, Derya; Gokce, Alper; Onal, Ayberk; Servet, Erkan; Dogan Ekici, Asiye Isın; Yener, Fatma Gulgun
Abstract: Biomimetic three-layered monolithic scaffold (TLS) intended for the treatment of osteocondral defects was prepared by using alginate, chitosan and β-tricalcium phosphate (β-TCP) to study drug release behavior of the alternative drug delivery system and to investigate the therapeutic efficacy of the scaffold. Dexamethasone sodium phosphate (Dex) as a model drug was incorporated into the scaffold by solvent sorption method and in vitro release studies were conducted. In addition, the scaffold was implanted into the defects formed in the trochlea of Sprague–Dawley rats to assess the healing potential of the TLS on the osteochondral defect against reference Maioregen® comparatively. The release studies showed that after an initial burst at 3rd h, dexamethasone is released slowly during a 72-h period. In vivo studies indicated that the TLS has good tissue biocompatibility and biodegradation rate and showed better results during osteochondral healing process compared to the reference. All results demonstrated that the alginate-chitosan/β-TCP scaffold could be evaluated as a good candidate for osteochondral tissue applications.